Genome : the autobiography of a species in 23 chapters - Ridley, Matt (London : Fourth Estate Limited, 1999)
The human genome, the complete set of genes housed in twenty-three pairs of chromosomes, is nothing less than an autobiography of our species. Spelled out in a billion three-letter words using the four-letter alphabet of DNA, the genome has been edited, abridged, altered and added to as it has been handed down, generation to generation, over more than three billion years. With the first draft of the human genome due to be published in 2000, we, this lucky generation, are the first beings who are able to read this extraordinary book and to gain hitherto unimaginable insights into what it means to be alive, to be human, to be conscious or to be ill.
Life -- Species -- History -- Fate -- Environment -- Intelligence -- Instinct -- Conflict -- Self-interest -- Disease -- Stress -- Personality -- Self-assembly -- Pre-history -- Immortality -- Sex -- Memory -- Death -- Cures -- Prevention -- Politics -- Eugenics -- Free will.
Includes bibliographical references : (pages 314-336) and index.
Keywords: Human genome -- Popular works; Human genetics -- Popular works